Assessment of Gingival Status and Gingival Overgrowth among Immunosuppressed Patients in Universiti Sains Malaysia Hospital - Wan Mohamad, Wan Majdiah; Mat Zaid, Syamimi Izzati; Taib, Haslina (UI Scholars Hub, 2021)
Drug-induced gingival overgrowth (DIGO) is defined as an abnormal growth of the gingiva due to adverse effect of some drugs such as immunosuppressant, calcium channel blocker, and anticonvulsant. Immunosuppressive drugs play an important role in controlling organ transplant rejection and were widely used to treat different diseases. Objective: Immunosuppressive drugs are used for prevention of transplant rejection and management of autoimmune disease. Drug-induced gingival overgrowth (GO) is abnormal growth of gingiva due to adverse effect of these drugs. This study aimed to assess the gingival status, the prevalence of gingival overgrowth and its associated factors among immunosuppressed patients. Methods: A total of 33 patients had participated in this cross-sectional study. Patients’ data such as age, race, gender, type of medication, and dosage were retrieved from patients’ medical record. Clinical oral examination was performed to assess the periodontal parameters: oral hygiene index, bleeding index and clinical gingival overgrowth index. Data were analysed using SPSS version 24.0. Results: The prevalence of gingival overgrowth among immunosuppressed patients is 57.6% at 95% confidence interval (40%,75%). Clinical index of gingival overgrowth shows 45.5% in grade 1 and 15.2% in grade 2. Oral hygiene status is significantly associated with gingival overgrowth based on plaque score (p= 0.01) and bleeding index score (p=0.05). Conclusion: The presence of gingival overgrowth among immunosuppressed patients is quite evidenced which could be contributed by poor oral hygiene.